Cybersecurity in Big Data Era: From Securing Big Data to Data-Driven Security - Manjunatha, V.; Shreedhara N, Hegde; Nur Fatin Liyana, Mohd Rosely (INTI International University, 2024)
In the age of information, the proverb "knowledge is power" has been shown to be true. admission to, which ultimately leads to knowledge acquisition. The relevance of the ability to glean knowledge from vast amounts of facts has increased. To describe the process of distributing, storing, and gathering enormous amounts of data for future analysis, researchers coined the term "big data analytics" (BDA). Data is generated at an alarming rate. The Internet of Things (IoT), the net's explosive expansion, and other technological advancements are the main forces behind this long-term growth. Since the information generated reflects the environment in which it is formed, the use of information gleaned from systems to understand the inner workings of those systems. The goal of protecting assets has been developed into a crucial component of cybersecurity. Additionally, big data now has the status of a high-value target due to the growing value of data. Current cybersecurity research in relation to big data has been reported here to explore big data security and its potential use as a cybersecurity tool. This gives trends, open research projects, and challenges along with a summary of current studies in the form of tables. In addition to current advancements and unanswered questions in this area of active research, this research work also provides readers a more thorough understanding of safety in the big data era.